Sengketa Tanah Akibat Perbuatan Melawan Hukum (Studi Kasus Putusan Pengadilan Negeri Sukoharjo No. 32/Pdt.G/2007/Pn.Skh) - Permana, Oktaviano Dian; , Darsono, SH, MH (2017)
Objective Is a Singer: 1) Knowing Settlement buying and selling land and buildings through claim deeds unlawfully in Sukoharjo. 2) Know the legal consequences of verdict Dispute Regarding buying and selling land and buildings in Sukoharjo district court. Based on the findings of the analysis tin conclusion that: 1) the Settlement buying and selling land and buildings through claim deeds unlawfully in Sukoharjo district court No. 32/Pdt.G/2007/Pn.Skh That letter was based at plaintiff's claim that linked with tool evidence and the testimony, in which the bounds of the object dispute the plaintiff's claim hearts letter attributed with facts revealed at the hearing has difference turns on limit northern and south side. By therefore based Considerations differences are in the judges concluded that the plaintiff's claim not clear, and plaintiff's claim must otherwise can not be accepted. 2) The legal consequences that case arose differences decision No. 32/Pdt.G/2007/Pn.Skh Against the disputing parties according to the Author's opinion is hearts Implementation of the decision, those plaintiffs not received by decision court of first instance can be filed Efforts legal appeal, appeal and Judicial Review.